Good wives, nasty wenches, and anxious patriarchs - Brown, Kathleen M (Published for the Institute of Early American History and Culture by the University of North Carolina Press, 1996)
Includes bibliographical references and index; Neal A. Newfield, Ph.D., LICSW (Giver)